Optimizing the wiring sequence based on a Constraint Satisfaction Problem for robot-based manufacturing of solderless wrapped connections - Hefner, Florian; Schmidbauer, Simon; Franke, Jörg (Procedia CIRP, 2022)
The manufacturing of solderless wrapped connections in traceable and reproducible high quality requires an automated manufacturing process. However, one key challenge for robot-based wiring is the definition of wiring sequence, as the proximity of the array-oriented wrapposts exacerbates tool accessibility. In this research, we optimize the wiring sequence by treating it as a constraint satisfaction problem, whereby a solution is indispensable, even if the constraints are not fulfilled. Experiments on a pilot plant for robot-based manufacturing of wrapped connections show that the percentage of automatically wired connections can be significantly increased with the developed approach.
CRIS-Team Scopus Importer:2022-12-09
Keywords: automation; Constraint Satisfaction Problem; control cabinet; lightweight robot; solderless wrapped connection; sorting algorithm; wiring

Pose error correction of a robot end-effector using a 3D visual sensor for control cabinet wiring - Hefner, Florian; Schmidbauer, Simon; Franke, Jörg (Procedia CIRP, 2020)
The wiring of control cabinets in small and medium-sized enterprises is a mostly manually performed process and very time-consuming. Thus, an automated approach for wiring control cabinets is necessary. The proposed solution is based on an ECAD model and performed by a lightweight robot. Before the wire insertion, the tip pose of the gripped wire end and the component port pose are detected by processing 3D sensor data. The sensor is able to detect wire ends with arbitrary cross-section geometries and arbitrary component port shapes. The results prove the functionality of correcting the pose of the robot end-effector with respect to a component port using a 3D sensor.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Automated control cabinet wiring; Flexible manufacturing; Pose correction; Position-based visual servoing; Robot-based automation

Vision-based adjusting of a digital model to real-world conditions for wire insertion tasks - Hefner, Florian; Schmidbauer, Simon; Franke, Jörg (Procedia CIRP, 2020)
In small and medium-sized enterprises, the wiring of control cabinets is a very time-consuming process as it is mostly performed manually. Thus, a novel automated approach for wiring control cabinets with batch size 1 is provided. The task is executed by a lightweight robot and based on an ECAD model of a wired cabinet. Therefore, a method is described to export digital data from ECAD and adjust the digital information to real-world conditions. To detect the approximate real-world poses of the components, a 2D image from a stationary visual sensor is used for CAD-based template matching by normalized cross-correlation. A high accurate visual 3D sensor that is mounted on the robot end-effector is moved to the approximate poses of the component ports to measure the exact poses. The results prove the functionality of the developed method, which allows to position the robotic end-effector based on ECAD data, which is the prerequisite to measure the component port with high accuracy using the 3D sensor.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Automated control cabinet wiring; ECAD; Flexible manufacturing; OpenCV; Robot-based automation; Template matching